Air, water, land: mexican-origin adolescents' perceptions of health and the environment - Carolyn M. Garcia; Marcelo Medeiros (Universidade Federal de Goias, 2007)
Latino adolescents are the fastest growing population sub-group in the United States (U.S.). Health disparities exist between Latino teens and the majority population of adolescents in the U.S. as evidenced by rates of health problems including asthma and depression; environmental factors contribute to these concerning trends. The objective is to describe how environmental influences are perceived by Mexican-origin immigrant adolescents. A focused ethnography guided by an ecological framework and symbolic interactionism was conducted using 1-to-1 interviewing, participant observations, and visual narratives created using disposable cameras. Fourteen participants took "pictures of life as an immigrant Latino adolescent, with a focus on health." Interview and photograph data were organized and analyzed using Atlas.ti software. Four themes were identified: "Garbage is everywhere," "Work hurts me," "Air we breathe," and "Relaxation in nature." Findings demonstrate comprehensive appreciation for risk and protective environmental influences on health. Nurses can utilize findings to reinforce the need to holistically assess Latino adolescent health, examining risk and protective environmental factors in the context of social determinants of health and health disparities. Findings support use of photovoice in research and that nursing theory can advance the ecological model and understanding of environmental health influences on disparities and well-being.